Response of sheep fed on corn cob silage or elephant grass basal diet with or without Calliandra leaf meal supplementation - Dwi Yulistiani (Jurnal Ilmu Ternak dan Veteriner, 2016)
Limited availability of forage diet throughout the year could be overcome by utilization of crop by-products. Corn cob, a by-product from maize production is potential to be used as a fiber source for grass replacement. The objective of the study was to compare the effect of two different basal diets (basal grass diet and corn cob silage) with or without Calliandra supplementation on feed intake, nutrient digestibility, nitrogen utilization, rumen fermentation and growth of sheep. The study used 20 male sheep St Croix breed. The sheep were divided into 5 groups based on body weight. Each group was fed with one of four diet treatments for 13 weeks. The treatments were grass basal diet + concentrate, Corn cob silage (CCS) + concentrate, Grass basal diet + concentrate + 5% Calliandra leaf meal, CCS + concentrate + 5% Calliandra leaf meal. The ratio of basal diet (grass or CCS) to concentrate was 40 : 60% and was formulated in iso protein (crude protein content 14%). The diet was offered in total mix ration. The experiment was conducted in a randomized complete block design and arranged in factorial 2 x 2 (2 type basal diets and 2 Calliandra supplementation levels) with 5 replications. Results showed that there was no interaction between basal diet and Calliandra supplementation on feed consumption, average daily gain (ADG), nutrient digestibility, rumen fermentation, except for crude protein (CP) intake. Feed consumption was not affected by basal diets or Calliandra supplementation. Feed conversion ratio and protein conversion ratio were better in grass basal diet than CCS. CP digestibility was higher in corn cob silage than basal grass diet without Calliandra supplementation. N retention was higher in corn cob basal diet than basal grass diet. Rumen fermentation was significantly affected by basal diet in which rumen ammonia and VFA concentrations were higher in grass basal diet. Grass basal diet had higher propionic acid production than CCS basal diet. From this study, it could be concluded that in iso protein diet, basal grass diet was comparable to corn cob basal diet as revealed by average daily gain was similar in both diets with average 107.5 g/head/day. Calliandra supplementation at 5% in the grass or CCS basal diet did not improve sheep performance.